Covid-19 Prevention (Study of Covid-19 Protocol and Relationship of Wudhu) - Saefulloh, Ahmad; Famularsih, Sari; Syarif, Mellyarti; Adimarta, Teguh; Helmy, Muh Irfan (The Journal of Society and Media, 2021)
Through the media of the time Efforts to prevent Covid-19 are currently closely related to the advice of Muslims against hygiene orders Various efforts are currently being made by all governments in the world in preventing and breaking the chain of distribution of co-19. Ranging from large-scale organizations namely international level such as WHO to small-scale organizations, namely in the family. All efforts made are inseparable from the sincerity of each individual who maintains that role. This article is motivated by the need to prevent the spread of Covid-19 from the viewpoint of the teachings of Islam. The purpose of this article is to study of covid-19 protocol policy and its relationship on internalization of wudhu ’as an effort to prevent through the literature study method in the form of Government policies and various institutions that issue circulars related to the Covid-19 prevention protocol. The results of this study found that every policy or circular issued, entirely emphasizes and regulates clean and healthy lifestyles by always washing hands thoroughly. So, Wudhu as a disciplinary activity for Muslims whose implementation is inseparable from washing hands. So this study is a form of emphasis on clean and healthy lifestyle in preventive efforts.